Carbon nanosheet loaded with atomic-scale active sites, diaphragm, aqueous zinc-halogen battery and preparation method of aqueous zinc-halogen battery

By using carbon nanosheet separators loaded with atomic active sites in zinc-halogen batteries, the problems of self-discharge and shuttle phenomena in zinc-halogen batteries are solved, and the efficient cycle stability and anti-self-discharge capability of the battery are improved.

CN119569037APending Publication Date: 2025-03-07SOUTH CHINA NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411263718.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In practical applications, zinc-halogen batteries face problems such as poor conductivity of bromine and iodine elements and slow conversion reaction kinetics. In particular, severe self-discharge effects and spontaneous shuttle phenomena lead to irreversible loss of active substances, reduced discharge platform and significant reduction in Coulomb efficiency.

Method used

Carbon nanosheets supported with atomic active sites are used as separator materials, and the retention-adsorption-catalysis of the multiiodide/polybromide is achieved through the atomic-scale dispersed pairs of single atoms Zn, single atom Mn and Zn-Mn atoms, preventing them from reaching the zinc negative electrode and converting them into an active substance I-/Br- that can provide capacity.

Benefits of technology

It effectively suppresses the self-discharge phenomenon, improves the cycle stability and anti-self-discharge capability of zinc halogen batteries, and significantly improves the specific capacity and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569037A_ABST
    Figure CN119569037A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon nanosheet loaded with atomic-scale active sites, a diaphragm, a water-based zinc halogen battery and a preparation method of the water-based zinc halogen battery, the carbon nanosheet is loaded with monatomic Zn, monatomic Mn and Zn-Mn atom pair active sites, the carbon nanosheet is used on the diaphragm and assembled into the water-based zinc halogen battery, the monatomic Mn is responsible for adsorbing a halogen reaction intermediate on the positive electrode side, and the monatomic Mn is responsible for adsorbing a halogen reaction intermediate on the negative electrode side. The Zn-Mn atom pair further catalyzes and converts the intermediate products into I- / Br-in time, so that the utilization rate of halogen species is increased, irreversible loss of active species of a halogen positive electrode is prevented, and the capacity retention rate is increased; the coulombic efficiency of the assembled zinc-halogen (Zn-I2) battery can still be maintained at 90.15% after the assembled zinc-halogen (Zn-I2) battery is charged and stands for 120 hours, and the self-discharge resistance of the battery is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aqueous zinc ion batteries, and in particular to a carbon nanosheet loaded with atomic-level active sites, a diaphragm, an aqueous zinc halogen battery and a preparation method thereof. Background Art

[0002] To meet the needs of sustainable development, people have an increasing demand for electrical energy storage, which has promoted the research and development of new battery systems. Among them, aqueous zinc-ion batteries (AZIBs) are economically competitive in large-scale energy storage due to their high safety and low cost. As an important component of AZIBs, the zinc metal anode exhibits a high specific capacity (820 mAh g -1 ), high volume capacity (5855mAhcm -3 ) and a suitable working potential (-0.762Vvs SHE) in aqueous electrolytes. Compared with traditional cathode materials for zinc-ion batteries (such as manganese oxide / vanadium oxide, MXenes, Prussian blue, MOFs and organic polymers), when halogens (bromine and iodine) are used as conversion cathodes, they have higher theoretical specific capacities (335 / 211mAh g -1 ) and redox potential (1.84 / 1.38V vs Zn 2+ In addition, zinc-bromine / iodine batteries have the great advantage of abundant reserves. The concentration of iodine in seawater is 50-60 μg L -1 , the concentration of bromine is 65 mg L -1 However, zinc-halogen batteries still face some inevitable challenges in practical applications, such as poor conductivity of bromine and iodine elements and slow conversion reaction kinetics. Among these problems, severe self-discharge effect and spontaneous shuttling phenomenon are the most difficult problems of zinc-halogen batteries. These phenomena can lead to irreversible loss of active materials, lower discharge platform and significantly reduced Coulombic efficiency.

[0003] Therefore, the present invention proposes a novel multifunctional diaphragm, which is modified with atomically dispersed metal active sites to prevent direct contact between polyiodide / polybromide and the zinc negative electrode, and can solve the self-discharge problem from both thermodynamic and kinetic perspectives. Summary of the invention

[0004] The primary purpose of the present invention is to provide a carbon nanosheet loaded with atomic-level active sites, wherein the carbon nanosheet is loaded with multiple atomic-level active sites, wherein the active sites include single-atom Zn, single-atom Mn and Zn-Mn atomic pairs, wherein the single-atom Mn active sites are responsible for adsorption, and the Zn-Mn atomic pairs are responsible for catalysis. The carbon nanosheet is prepared into a diaphragm and used in an aqueous zinc-halogen battery. Thanks to these atomic-level dispersed active sites, through an effective interception-adsorption-catalysis strategy, the iodine species polyiodide / polybromide that originally shuttled to the zinc negative electrode side is effectively adsorbed on the diaphragm and further converted into an active substance I that can provide capacity. - / Br - , thereby preventing it from reaching the zinc negative electrode, the utilization rate of the cathode active material is significantly improved, the self-discharge phenomenon is suppressed, and the performance of the battery is improved.

[0005] The present invention at least provides the following technical solutions:

[0006] On one hand, the present invention provides a carbon nanosheet loaded with atomic-level active sites, wherein the carbon nanosheet is loaded with multiple atomic-level active sites, wherein the active sites include single-atom Zn, single-atom Mn and Zn-Mn atomic pairs; the carbon nanosheet is leaf-shaped, especially elliptical leaf-shaped.

[0007] In one aspect, the present invention provides a method for preparing carbon nanosheets loaded with atomic-level active sites, comprising the following steps:

[0008] A certain amount of 2-methylimidazole and zinc nitrate hexahydrate are dissolved in deionized water to form a ligand solution A and a zinc source solution B of a certain concentration;

[0009] A certain amount of manganese source is dissolved in solution B, and then solution B is mixed and stirred with solution A for 1-4 hours, and then allowed to stand for 5-12 hours to obtain product A;

[0010] Then, the product A is dissolved in an aqueous solution of ethanol, centrifuged and dried at a certain temperature to obtain product B;

[0011] A certain amount of product B is dissolved in a certain volume of N,N-dimethylformamide ethanol solution, then kept at 60-80°C for 48-56 hours, centrifuged to remove the solvent, and dried to obtain a ZIF-8 / Mn precursor;

[0012] The ZIF-8 / Mn precursor is heated to 400°C~600°C at a certain rate, kept warm for 1-3 hours, then heated to 900°C~1000°C in an inert atmosphere, kept warm for 1-3 hours, then naturally cooled to room temperature, and then washed with a certain concentration of hydrochloric acid solution to remove impurities. After drying, carbon nanosheets loaded with atomic-level active sites of single-atom Zn, single-atom Mn and Zn-Mn atomic pairs are obtained.

[0013] Furthermore, single-atom Zn active sites account for 1.8-4.0 wt% of the carbon nanosheets.

[0014] Furthermore, the single-atom Mn active sites account for 0.2-1.0 wt% of the carbon nanosheets.

[0015] Furthermore, the Zn-Mn atomic pair active sites account for 0.1-0.8 wt % of the carbon nanosheets.

[0016] One aspect of the present invention provides a diaphragm, which includes a diaphragm substrate, on which the above-mentioned carbon nanosheets are loaded.

[0017] Furthermore, the amount of the carbon nanosheets loaded on the diaphragm substrate is 0.24-0.35 mg / mm 2 .

[0018] Furthermore, the membrane matrix is ​​a polytetrafluoroethylene membrane, a polypropylene membrane or a glass fiber membrane.

[0019] Another aspect of the present invention provides an aqueous zinc-halogen battery, comprising a diaphragm, wherein the diaphragm is the diaphragm described above.

[0020] Further, the manganese source is selected from any one of manganese chloride, MnCl2·4H2O, manganese nitrate, manganese sulfate, and manganese acetate;

[0021] Furthermore, the manganese source is MnCl2·4H2O, and the amount of MnCl2·4H2O dissolved in solution B is 0.1 mmol to 1.5 mmol.

[0022] Further, the manganese source is MnCl2·4H2O, and the molar ratio of 2-methylimidazole, zinc nitrate hexahydrate and MnCl2·4H2O is 7:1:0.3;

[0023] The mass ratio of product B to N,N-dimethylformamide is 1:320.

[0024] Compared with the prior art, the present invention has at least the following beneficial effects:

[0025] The present invention provides a carbon nanosheet with atomically monodispersed active sites, wherein the active sites include single-atom Zn, single-atom Mn and Zn-Mn atomic pairs, and the content of the active sites is precisely controllable. The active sites have a synergistic effect and play a good interception-adsorption-catalysis function for polyhalogen intermediates. The carbon nanosheet of the present invention is used on a diaphragm material to obtain a modified diaphragm, and the modified diaphragm exhibits a universal strategy in zinc-iodine / bromine batteries.

[0026] On the other hand, the modified diaphragm exhibited excellent specific capacity and rate performance when applied to zinc-iodine / bromine batteries.

[0027] The preparation method of the present invention adjusts the Mn doping ratio, maintains the morphology of the nanosheets by low-temperature calcination, and evaporates the metal salt by high-temperature calcination, thereby obtaining a carbon nanosheet loaded with multiple atomic-level active sites of Zn and Mn. The carbon nanosheet is used to modify the diaphragm material on the diaphragm material. The prepared diaphragm effectively improves a series of problems faced by the zinc-halogen battery during the cycle process, especially improves the self-discharge problem of the zinc-halogen battery, effectively inhibits the serious shuttling of poly-iodine / poly-bromine species, promotes the cycle stability of the aqueous zinc-halogen battery and significantly improves the self-discharge resistance of the zinc-halogen battery, laying a solid foundation for the development of aqueous zinc-halogen batteries.

[0028] In one embodiment of the present invention, the zinc-iodine battery assembled with the modified ZnMn-NC / GF membrane has a coulombic efficiency of up to 90.15% after standing for 120 hours after charging. The soft-pack battery assembled with the membrane can drive a toy car for 11 minutes and can also provide stable energy for a small fan. The static zinc-bromine battery assembled with the modified ZnMn-NC / GF membrane can be used at 5A g -1 The battery was cycled 3000 times at a current density of 1.50 W with no obvious capacity decay. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Figures 1 and 2 are performance test diagrams of the carbon nanosheets prepared in Example 1 of the present invention, wherein Figure a is a diagram showing the mechanism of action of an ordinary glass fiber membrane and polyiodide; Figure b is a diagram showing the mechanism of action of a diaphragm of a carbon nanosheet loaded with atomic-level active sites provided by the present invention and polyiodide; Figure c is a SEM image of the Zn-NC prepared in Example 1; Figure d is a SEM image of the ZnMn-NC prepared in Example 1; Figures e and f are TEM images of Zn-NC and ZnMn-NC, respectively; Figures g and h are spherical aberration images of ZnMn-NC at different magnifications; Figures i and j are XRD and Raman images of Zn-NC and ZnMn-NC, respectively; Figures k and l are line scanning intensity distribution diagrams corresponding to the bright spots in the spherical aberration image of ZnMn-NC in Figure g; and Figure m is an element distribution diagram of ZnMn-NC.

[0030] Figure 2These are synchrotron radiation test images of the carbon nanosheets obtained in Example 1, wherein a and b are the x-ray near-edge absorption spectra of materials Zn-NC and ZnMn-NC, respectively; c and d are the fine absorption spectra (EXAFS) images of the two materials, reflecting the coordination environment of metal Zn and Mn; e and f are the EXAFS fitting results of ZnMn-NC material in R space; g and h are wavelet transform images of Zn-NC and ZnMn-NC, which further confirm that metal Zn and Mn exist in atomic form and form additional ZnMn-N6 atomic pairs.

[0031] Figure 3 The Zn-I2 battery is assembled from carbon nanosheets prepared from precursors with different manganese contents. -1 Performance comparison under different current densities.

[0032] Figure 4 The voltage-capacity curves of the zinc-iodine battery with a ZnMn-NC / GF separator assembled in Example 3 of the present invention when tested at different current densities.

[0033] Figure 5 It is a comparison chart of the voltage drop of zinc-iodine batteries with different diaphragms assembled in Example 3 of the present invention after standing for 120 hours.

[0034] Figure 6 This is a comparison chart of the decrease in the median discharge voltage of the zinc-iodine batteries with different separators assembled in Example 3 of the present invention after being left standing for 120 hours.

[0035] Figure 7 The zinc-iodine batteries with different diaphragms assembled in Example 3 of the present invention were tested at current densities of 1A g -1 , 5A g -1 Comparison of cycle performance under test conditions.

[0036] Figure 8 This is an electrochemical performance diagram of the zinc-iodine soft-pack battery with a ZnMn-NC separator prepared in Example 3 of the present invention.

[0037] Fig. 9 This is a long cycle comparison diagram of zinc-bromine batteries with different separators assembled in Example 3 of the present invention.

[0038] Fig.10 This is a schematic diagram of the zinc-iodine soft-pack battery with a ZnMn-NC membrane prepared in Example 3 of the present invention driving a fan to operate stably.

[0039] Fig.11 This is a comparison chart of the rate performance of zinc-iodine batteries with different diaphragms assembled in Example 3 of the present invention. DETAILED DESCRIPTION

[0040] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention. The experimental methods described in the following embodiments are all conventional methods unless otherwise specified; the reagents and materials, unless otherwise specified, can be obtained from public commercial channels.

[0041] Spatially relative terms such as "below," "beneath," "below," "above," "upper," etc. are used in this specification to explain the positioning of one element relative to a second element. These terms are intended to encompass different orientations of the device in addition to different orientations than those depicted in the figures.

[0042] In addition, the use of terms such as "first", "second", etc. to describe various elements, layers, regions, sections, etc. is not intended to be limiting. The use of "having", "containing", "including", "comprising", etc. is open-ended, indicating the presence of the stated elements or features, but does not exclude additional elements or features. Unless the context clearly states otherwise.

[0043] The term "high purity" used in this specification means a purity of 99.99% or more.

[0044] Example 1

[0045] 2-Methylimidazole (1160 mg, Aladdin, analytical grade) and zinc nitrate hexahydrate (520 mg, Aladdin, analytical grade) were dissolved in deionized water (40 ml) to form solutions A and B, respectively. Then, different molar amounts of MnCl2·4H2O (0 mmol, 0.263 mmol, 0.525 mmol, 1.05 mmol and 1.575 mmol, Aladdin, 99.99%) were uniformly dissolved in solution B, and solution B was quickly poured into solution A and stirred vigorously for two hours. After standing for 12 hours, the products were obtained. These products were centrifuged at 8000 rpm for 3 minutes with water and ethanol, and then dried at 60°C for 12-24 hours. 0.5 g of the dried product was taken and placed in a mixed solution of 160 ml of ethanol and N,N-dimethylformamide (DMF), with a volume ratio of ethanol to DMF of 1:3, and kept at 70°C for 48 hours. Subsequently, the solvent was removed by centrifugation and dried at 60 °C overnight to obtain ZIF-8 precursor without Mn and ZIF-8 / Mn precursors with different Mn contents.

[0046] The ZIF-8 precursor and ZIF-8 / Mn precursor were heated to 500°C at a rate of 5°C / min for 1 hour to maintain the morphology of the ZIF-8 nanosheets, and then heated to 900°C in a nitrogen atmosphere for 2 hours to evaporate the metal salts to obtain atomic-level active sites, and then naturally cooled to room temperature. Washed with 1M hydrochloric acid solution to remove impurities and dried at 60°C overnight, the carbon nanosheets loaded with metal atoms were prepared. The product prepared containing 0.525mmol MnCl2·4H2O was labeled as ZnMn-NC.

[0047] The carbon nanosheets prepared above were tested for their performance. Figure 1 The SEM and TEM images show that the prepared carbon nanosheets have a leaf-like morphology of about 3 μm in length, and metal atoms of different brightness are evenly dispersed on the carbon nanosheets. Figure 1 The g and h images in the figure show metal atoms with different brightness. Synchrotron radiation tests were used to further accurately determine the existence forms of metal Zn and Mn on carbon nanosheets, such as Figure 2 As shown in the figure, the X-ray near-edge absorption spectrum and fine structure spectrum (Mn and Zn) of the metal were collected respectively. It can be seen from Figures a and b that the valence states of the metal elements Zn and Mn are respectively at 0-+2 and 0-+3. Figures c and d reflect that the scattering paths of the elements Zn and Mn are different from those of metal Zn and Mn, and also different from the scattering paths of metal oxides, indicating that the metal Zn and Mn in the material exist at the atomic level, and the secondary peaks in Figures c and d reflect the existence of Zn-Mn atomic pairs. Figures g and h further confirm that the metal Zn and Mn exist at the atomic level and form additional ZnMn-N6 atomic pairs.

[0048] The weight ratio of Zn and Mn elements in the ZnMn-NC test was measured by inductively coupled plasma optical emission spectrometry (ICP-OES). The results are shown in Table 1.

[0049] Table 1

[0050]

[0051] Example 2

[0052] The ZnMn-NC material and carboxymethyl cellulose prepared in Example 1 were dissolved in deionized water at a mass ratio of 9:1 and ground into a slurry, which was evenly coated on a glass fiber membrane (GF) and dried at 60°C to obtain a modified fiber membrane ZnMn-NC / GF membrane.

[0053] The Zn-NC material and carboxymethyl cellulose prepared in Example 1 were dissolved in an appropriate amount of deionized water in a mass ratio of 9:1 and ground into a slurry, which was evenly coated on a glass fiber membrane (GF) and dried at 60°C to obtain a modified fiber membrane Zn-NC / GF membrane.

[0054] Select high-purity zinc foil with a purity of 99.99% and a thickness of 0.1 mm. Remove the oxide layer on the surface of the zinc foil, and use 800-mesh sandpaper and 2000-mesh sandpaper to polish the zinc foil to remove the oxide layer on the surface. After polishing, use alcohol to scrub repeatedly to ensure that there is no impurity residue on the surface and obtain a bright surface.

[0055] Example 3

[0056] Activated carbon, conductive carbon black and PVDF binder were weighed in a weight ratio of 7:2:1, mixed, ground and stirred evenly, and coated on graphite paper with a scraper. The slurry was 150 μm thick and dried in a vacuum oven at 60°C. After drying, a pole piece with a diameter of 1.4 cm was cut to serve as a positive pole piece loaded with iodine species. The positive pole piece was soaked in a 0.5M ZnI2 solution for 1 hour, taken out and dried in a vacuum oven at 40°C to obtain an iodine positive pole. The modified fiber diaphragm ZnMn-NC / GF prepared in Example 2 was cut to obtain a diaphragm with a diameter of 1.6 cm. A 2M zinc sulfate aqueous solution was used as the electrolyte, and the negative electrode was the high-purity zinc foil with the above-mentioned bright surface, and a zinc-iodine battery was assembled.

[0057] The modified fiber separator Zn-NC / GF prepared in Example 2 was cut into a separator with a diameter of 1.6 cm. A zinc-iodine battery was assembled using a 2M zinc sulfate aqueous solution as the electrolyte, the iodine positive electrode as the positive electrode, and the high-purity zinc foil with the bright surface as the negative electrode.

[0058] Take the above-mentioned glass fiber separator GF and cut it into a separator with a diameter of 1.6 cm, use 2M zinc sulfate aqueous solution as electrolyte, the positive electrode is the above-mentioned iodine positive electrode, and the negative electrode is the above-mentioned high-purity zinc foil with a bright surface, and assemble a zinc-iodine battery as a comparative example of Example 3.

[0059] The carbon nanosheets prepared from the precursors with different manganese contents obtained in Example 1 were used to prepare a diaphragm under the conditions in Example 2, and then assembled into a zinc-iodine battery according to the above assembly conditions. Figure 3 As shown, at 0.5A g -1 According to the performance comparison of Zn-I2 batteries under the current density, we can see that when the dosage of MnCl2·4H2O is 0.525mmol, the discharge platform of the assembled battery is the longest and the discharge voltage is relatively high, indicating that the zinc-iodine battery assembled from the materials prepared under this condition has better performance.

[0060] Figure 4The voltage-capacity curve of the zinc-iodine battery assembled with the ZnMn-NC / GF separator was tested at different current densities. It can be seen that the voltage-capacity curve of the zinc-iodine battery assembled with the ZnMn-NC / GF separator was -1 Under the condition of current density of 20A g, the zinc-iodine battery assembled by ZnMn-NC / GF separator showed a stable discharge platform, even at 20A g -1 At high current density, the charge and discharge platform for iodine redox is also very obvious, showing an excellent reaction kinetics process.

[0061] Figure 5 The figure is a comparison of the voltage drop of the zinc-iodine battery with ZnMn-NC / GF membrane prepared in Example 3 of the present invention, the zinc-iodine battery with Zn-NC / GF membrane and the zinc-iodine battery with unmodified glass fiber membrane in the comparative example after standing for 120 hours. The test conditions are as follows: -1 At a current density of 1.6 V and a cut-off voltage of 1.6 V, the battery was left to stand for 120 hours after charging. The coulombic efficiencies of the batteries assembled with three different separators were 69.81%, 79.25% and 90.15% in ascending order.

[0062] Figure 6 This is a comparison chart of the decrease in the median discharge voltage of the three batteries in Example 3 after 120 hours of storage. Thanks to the synergistic effect of multiple active sites, the ZnMn-NC / GF membrane can effectively intercept, adsorb and catalyze polyiodine / polybromide, thereby effectively suppressing the self-discharge phenomenon. Under the same test conditions, the zinc-iodine battery assembled with the ZnMn-NC / GF membrane has the smallest decrease in median discharge voltage, which is only 20mV.

[0063] Figure 7 The three zinc-iodine batteries assembled in Example 3 were -1 , 5Ag -1 Under the test conditions, the zinc-iodine battery modified by ZnMn-NC exhibited excellent cycle stability and long cycle life. It could stably cycle 9000 times at low current density, and the capacity retention rate reached 95.9% after 30000 cycles at high current density.

[0064] Figure 8 The zinc-iodine soft-pack battery assembled with the ZnMn-NC modified diaphragm in Example 3 has a total capacity of 60 mAh when the current is 50 mA under the condition that the positive electrode iodine loading is 368.1 mg, and can be stably cycled 500 times.

[0065] Example 4

[0066] Activated carbon, KBr, conductive carbon black and PVDF binder were weighed in a weight ratio of 3:3:3:1, mixed, ground and stirred evenly, and coated on the hydrophobic carbon cloth with a scraper to a thickness of 150 μm. The slurry was dried in a vacuum oven at 60°C and cut into a pole piece with a diameter of 1.4 cm as a bromine positive electrode after drying.

[0067] The modified fiber diaphragm ZnMn-NC / GF prepared in Example 2 was cut into a diaphragm with a diameter of 1.6 cm. A zinc-bromine battery was assembled using a 2M zinc sulfate aqueous solution as the electrolyte, the above-mentioned bromine positive electrode as the positive electrode, and the above-mentioned high-purity zinc foil with a bright surface as the negative electrode.

[0068] The modified fiber diaphragm Zn-NC / GF prepared in Example 2 was cut into a diaphragm with a diameter of 1.6 cm. A zinc-bromine battery was assembled using a 2M zinc sulfate aqueous solution as the electrolyte, the above-mentioned bromine positive electrode as the positive electrode, and the above-mentioned high-purity zinc foil with a bright surface as the negative electrode.

[0069] Take the above-mentioned glass fiber separator GF and cut it into a separator with a diameter of 1.6 cm, use 2M zinc sulfate aqueous solution as electrolyte, the positive electrode is the above-mentioned bromine positive electrode, and the negative electrode is the above-mentioned high-purity zinc foil with a bright surface, and assemble a zinc-bromine battery as a comparative example of Example 4.

[0070] from Fig. 9 It can be seen that the Zn-Br2 battery assembled with ZnMn-NC / GF separator not only exhibits higher specific capacity, but also can -1 The battery was able to complete 3000 charge-discharge cycles at a current density of 1.5 % with no significant capacity decay. However, the unmodified separator failed after 920 cycles due to severe shuttling of bromine species.

[0071] Fig.10 This is a demonstration of the practical application of the soft-pack battery assembled from the zinc-bromine battery with the modified fiber separator ZnMn-NC / GF in Example 4. Three soft-pack batteries connected in series can stably provide energy for a small fan.

[0072] Fig.11 The zinc-bromine batteries with three different diaphragms in Example 4 are 0.5-15Ag -1 The rate performance test at current density showed that the zinc-bromine battery assembled with the ZnMn-NC / GF modified diaphragm always showed the highest specific capacity at different current densities, indicating that the diaphragm re-adsorbed and re-catalyzed polybromide to a large extent, thereby improving the utilization rate of active species in the bromine positive electrode.

[0073] The carbon nanosheets provided by the present invention having single-atom Zn, single-atom Mn and Zn-Mn atomic pair active sites can effectively adsorb polyiodides / polybromides, effectively inhibit the shuttling of halogen intermediates, improve the utilization rate of the halogen positive electrode, and greatly improve the anti-self-discharge ability of the aqueous zinc-halogen battery, thereby improving the cycle stability performance of the zinc-halogen (iodine / bromine) battery.

[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A carbon nanosheet loaded with atomic-level active sites, characterized in that: The carbon nanosheets are loaded with a plurality of atomic-level active sites, wherein the active sites include single-atom Zn, single-atom Mn and Zn-Mn atomic pairs.

2. A method for preparing carbon nanosheets loaded with atomic-level active sites, characterized in that: The steps include: A certain amount of 2-methylimidazole and zinc nitrate hexahydrate are dissolved in deionized water to form a ligand solution A and a zinc source solution B of a certain concentration; A certain amount of manganese source is dissolved in solution B, and then solution B is mixed and stirred with solution A for 1-4 hours, and then allowed to stand for 5-12 hours to obtain product A; Then, the product A is dissolved in an aqueous solution of ethanol, centrifuged and dried at a certain temperature to obtain product B; A certain amount of product B is dissolved in a certain volume of a mixed solution of N,N-dimethylformamide and ethanol, and then kept at 60-80°C for 48-56 hours, centrifuged to remove the solvent, and dried to obtain a ZIF-8 / Mn precursor; The ZIF-8 / Mn precursor is heated to 400°C~600°C at a certain rate, kept warm for 1-3 hours, then heated to 900°C~1000°C in an inert atmosphere, kept warm for 1-3 hours, then naturally cooled to room temperature, and then washed with a certain concentration of hydrochloric acid solution to remove impurities. After drying, carbon nanosheets loaded with atomic-level active sites of single-atom Zn, single-atom Mn and Zn-Mn atomic pairs are obtained.

3. The carbon nanosheet according to claim 1 or the preparation method according to claim 2, characterized in that: The single-atom Zn active sites account for 1.8–4.0 wt% of the carbon nanosheets.

4. The carbon nanosheet according to claim 1 or the preparation method according to claim 2, characterized in that: The single-atom Mn active sites account for 0.2–1.0 wt% of the carbon nanosheets.

5. The carbon nanosheet according to claim 1 or the preparation method according to claim 2, characterized in that: The Zn-Mn atomic pair active sites account for 0.1-0.8 wt% of the carbon nanosheets.

6. A diaphragm, comprising a diaphragm substrate, characterized in that: The diaphragm substrate is loaded with the carbon nanosheet according to any one of claims 1 and 3 to 5.

7. The diaphragm according to claim 6, characterized in that The diaphragm matrix is ​​a polytetrafluoroethylene membrane, a polypropylene membrane or a glass fiber membrane; Preferably, the amount of the carbon nanosheets loaded on the diaphragm substrate is 0.24-0.35 mg / mm 2 .

8. An aqueous zinc-halogen battery comprising a diaphragm, characterized in that: The diaphragm is the diaphragm according to claim 6 or 7.

9. The preparation method according to any one of claims 2 to 5, characterized in that: The manganese source is selected from any one of manganese chloride, MnCl2·4H2O, manganese nitrate, manganese sulfate and manganese acetate; Preferably, the manganese source is MnCl2·4H2O, and the amount of MnCl2·4H2O dissolved in solution B is 0.1 mmol to 1.5 mmol.

10. The preparation method according to claim 9, characterized in that: The manganese source is MnCl2·4H2O, and the molar ratio of 2-methylimidazole, zinc nitrate hexahydrate and MnCl2·4H2O is 7:1:0.3; The mass ratio of product B to N,N-dimethylformamide is 1:320.

Citation Information

Cited By

  • Manganese-doped nickel diselenide positive electrode material and preparation method and application thereof

    CN122314886A